2020
DOI: 10.1016/j.biocel.2020.105738
|View full text |Cite
|
Sign up to set email alerts
|

Viroporins and inflammasomes: A key to understand virus-induced inflammation

Abstract: J o u r n a l P r e -p r o o f Highlights  The article provides a summary on cellular receptors involved in virus immunity.  It presents an overview of the current understanding of inflammasomes complex activation, comparing its different types with special focus on NLRP3.  The article summarizes key findings on viroporins, a novel class of viral proteins and their role in the virus life cycle and host cell interactions.  The article sheds the light on the correlation between viroporins and inflammasomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 140 publications
(157 reference statements)
3
111
1
2
Order By: Relevance
“…Complications such as continuous stimuli or infections, such as viral infections, may worsen the prognosis of TBI, altering the immune response and increasing the related neuroinflammatory processes. Viral infections are often related to inflammation and virus proteins, as viroporins, may play a pivotal role in promoting viral infection [ 142 ]. Previous studies showed that viroporins promote NLRP3 inflammasome activation [ 142 , 143 ], in fact NLRP3 activation was observed following influenza A virus and SARS-CoV infections [ 144 ].…”
Section: Nlrp3 Inflammasome Sars-cov-2 and Possible Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications such as continuous stimuli or infections, such as viral infections, may worsen the prognosis of TBI, altering the immune response and increasing the related neuroinflammatory processes. Viral infections are often related to inflammation and virus proteins, as viroporins, may play a pivotal role in promoting viral infection [ 142 ]. Previous studies showed that viroporins promote NLRP3 inflammasome activation [ 142 , 143 ], in fact NLRP3 activation was observed following influenza A virus and SARS-CoV infections [ 144 ].…”
Section: Nlrp3 Inflammasome Sars-cov-2 and Possible Consequencesmentioning
confidence: 99%
“…Viral infections are often related to inflammation and virus proteins, as viroporins, may play a pivotal role in promoting viral infection [ 142 ]. Previous studies showed that viroporins promote NLRP3 inflammasome activation [ 142 , 143 ], in fact NLRP3 activation was observed following influenza A virus and SARS-CoV infections [ 144 ]. In the past few months and until now, a novel coronavirus, the SARS-CoV-2, is affecting the population worldwide, thus causing a high number of deaths so that the World Health Organization (WHO) has declared coronavirus disease 2019 (COVID-19) as global pandemic.…”
Section: Nlrp3 Inflammasome Sars-cov-2 and Possible Consequencesmentioning
confidence: 99%
“…Generated via the activation of the NLRP3 inflammasome, a multi-subunit complex comprising of the NLR protein NLRP3, the adaptor protein ASC and caspase-1, IL-1β promotes anti-microbial resistance via the modulation of innate and adaptive immune responses ( 65 ). However, if dysregulated, production of this pro-inflammatory cytokine can promote lung injury and severe pulmonary fibrosis ( 66 , 67 ).…”
Section: Pathogen Recognitionmentioning
confidence: 99%
“…The PNPLA3 missense variant rs738409Ile148Met) (C>G), causing loss of function, is associated with hyperexpression of the NLRP3 in ammosome, leading to increased serum levels of IL-1β and IL18 [18]. It is known that many viruses and among them SARS-CoV-2, are directly able to induce activation of the NRLP3 in ammosome leading to the cytokines storm probably causing most fatal outcomes [19]. In our subcohort of patients ≤65 years, the GG PNPLA3 genotype was signi cantly associated to an increased risk of severe outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit the pathogenetic mechanism of coronavirus disease 2019 (COVID- 19) is yet partly unclear, the course and outcome of disease seem to be signi cantly in uenced by host factors supporting a strong proin ammatory response and inducing a massive release of cytokines leading to a "cytokine storm" ultimately causing severe alveolar damage but also multiorgan failure [4]. It is thus conceivable that the complexity of host genetic background in terms of polymorphisms in genes involved in SARS-CoV-2 receptor-dependent endocytosis, antiviral responses and modulation of cell infection and reinfection, in ammation, or immune stimulation may play a key role in pathogenesis and outcome of COVID-19.…”
Section: Introductionmentioning
confidence: 99%